Epigenetic variations brought about by climatic change in plants – an assessment - PARUL SAKSENA,; ASHA AGARWAL, (International Journal of Pharma and Bio Sciences, 2017)
The earth is experiencing major changes in global and regional climates and changes are believed to escalate in the future. The organism will be facing the threat of extinction. Detoriating environment conditions can bring about epigenetics changes in plant and also in gene expression. This may help plants to adapt to environmental change. Also they are reversible.The major challenge for the investigation of epigenetic adaptation theories is therefore to identify genomic loci that undergo epigenetic changes in response to environmental conditions, which alter their expression in a heritable way and which improve the plant’s ability to adapt to the inducing conditions. This review focuses on the role of DNA methylation as a prominent epigenetic mark that controls chromatin conformation, and on its potential in mediating expression changes in response to environmental signals.